PENINGKATAN KONSENTRASI DAN HASIL BELAJAR MELALUI MIND MAPPING SISWA KELAS V SDN PASIRMANGGU - Lisa Humaeroh; Ayu Khairunnisa; Malek Tipagau; Ujang Jamaludin; Sigit Setiawan (STKIP Subang, 2023)
This study aims to determine the increase in concentration and learning outcomes in science through mind mapping for class V SDN Pasirmanggu. This research is motivated by the presence of students who do not concentrate during the learning process so that it affects learning outcomes that are not optimal. This study used a type of classroom action research in which the subjects were 18 fifth grade students at SDN Pasirmanggu. while the object of this research is to increase learning concentration and science learning outcomes through mind mapping in class V SDN Pasirmanggu. The instrument of this research was to use a questionnaire sheet to measure the level of student learning concentration and an observation sheet to observe students and teachers in the science learning process by applying the mind mapping method. Research data were analyzed by descriptive qualitative and quantitative. The results of this study indicate that learning through the application of the mind mapping method can improve concentration and science learning outcomes in fifth grade students at SDN Pasirmanggu. By modifying actions in the form of delivering material using a modified mind mapping method, questioning and answering material by actively involving students, making and creating mind map forms accompanied by teachers and researchers, presenting the results of student mind maps by selecting them randomly, and reflecting on learning by involving students at the end of learning, able to increase learning concentration and student learning outcomes. Based on the results of questionnaires and observations, the concentration of students' learning has increased with the